Rancang Bangun Game Edukasi Eksplorasi Wisata dan Budaya Tasikmalaya - Anwar, Dede Syahrul; Mufizar, Teuku; Shafarulloh, M. Hisyam; Maulana, Akmal (LPPM Universitas Potensi Utama, 2025)
Tasikmalaya, a region rich in tourism and cultural diversity, is still not widely recognized by the public. In the digital era, interactive media such as games can serve as an effective tool to introduce and promote its potential. This research focuses on designing and developing an educational adventure game that explores the tourism and cultural aspects of Tasikmalaya. The novelty of this study lies in its interactive and educational approach, specifically designed to educate users, particularly the younger generation, about Tasikmalaya's tourist attractions and cultural heritage. By utilizing game technology, it is expected to provide an engaging and informative learning experience.The research method used is the Multimedia Development Life Cycle (MDLC). The concept stage involves identifying the game's needs and objectives. The design stage includes story development, character creation, and user interface design. The material collection stage focuses on gathering necessary information and media assets. The assembly stage involves the technical development of the game. Testing is conducted to ensure the game's quality and functionality, while the distribution stage delivers the game to users.The final result of this research is an educational game aimed at enhancing public knowledge and appreciation of Tasikmalaya's tourism and culture, while also contributing to scientific development through research publication.